‘Coming out’ of Thai students in the Discourse of Higher Education - Panapa Chintaradeja (Gemilang Maju Publikasi Ilmiah (GMPI), 2021)
This study aims to explain coming out of Thai students in the discourse of higher education. Thus, prior research and literature reviews are discussed and argued critically to extend the knowledges of “coming out”. The in-depth interview is employed to be the method for gathering data from Thai university students in the discourse of higher education by using purposive sampling. Lastly, the finding is contented and analyzed into narrative description.